Oxidative Stress Delays Prometaphase/Metaphase of the First Cleavage in Mouse Zygotes via the MAD2L1-Mediated Spindle Assembly Checkpoint. (25th September 2017) - Wu, Que; Li, Zhiling; Huang, Yue; Qian, Diting; Chen, Man; Xiao, Wanfen; Wang, Bin
Abstract : In zygotes, DNA damage delays the first cleavage to enable repair. Our previous study found that 0.03 mM hydrogen peroxide (H2 O2 ) was the minimum concentration required for induction of oxidative DNA damage in mouse zygotes and that this represented the most similar situation to the clinical phenomenon. In this study, we quantified the cleavage rates of cells in blastocysts at different developmental stages, followed by immunofluorescence to detect activation of γ -H2A histone family member X (a marker of DNA damage) in zygotes to confirm that oxidative DNA damage was induced in H2 O2 -treated zygotes. Monitoring H3S10P (phosphorylation of Ser10 on histone H3; a prometaphase/metaphase marker) levels at different hour postinsemination revealed that treatment of zygotes with 0.03 mM H2 O2 resulted in a prometaphase/metaphase delay. Furthermore, immunofluorescence staining for mitotic arrest deficient 2-like 1 and the protein kinase TTK, components of the spindle assembly checkpoint (SAC), suggested that this delay possibly involved SAC activation. These studies of the relationships between oxidative stress and SAC can promote the success rate of in vitro fertilization.